Peran Notaris Dan Perlindungan Hukum Dalam Perjanjian Jual Beli Bekas Tanah Kas Desa Pandowoharjo Sleman - Ivan Novian Janitra (Lex Renaissance, 2020)
This study aims to determine the role of a notary and legal protection for the sale and purchase of rights to land former treasury land in Pandowoharjo Village, where the formulation of the problems posed are: First, how is the legal protection for sellers and buyers in buying and selling rights to land former village treasury lands in Pendowoharjo Village which was made under-hand?; Second, what is the role of the notary in the settlement of the sale and purchase of rights over the former treasury land of Pendowoharjo Village which was made under-hand? This research is descriptive-qualitative, in which data is collected by interviewing the Sleman Regency Land and Spatial Planning Office, Pandowoharjo Village Administration, Pandowoharjo Residents and Notaries in Sleman Regency, as well as studying and reviewing laws and regulations, library books and other documents related to research. The results of this study concluded that legal protection was carried out by the Pandowoharjo Village Government by facilitating the under-hand sale and purchase to be witnessed by village officials and the Chief of Village; Additionally, the author suggests that the role of the Notary can be involved in order to strengthen the evidenciary power of the underhand agreement by legalizing the sale and purchase agreement letter of the former treasury land of Pandowoharjo Village.